2007
DOI: 10.1080/13625180600983082
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of an oral contraceptive containing drospirenone in the treatment of women with polycystic ovary syndrome

Abstract: The combined oral contraceptive containing 30 microg ethinyloestradiol and 3 mg drospirenone is an effective drug in the treatment of hyperandrogenism in women with PCOS; it elicits few side effects and does not significantly influence insulin resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
8

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 17 publications
1
34
0
8
Order By: Relevance
“…However, the metabolic effects of pills are extremely variable, depending on the dose of ethinyl E 2 (EE) and on the type of progestin associated. Drospirenone (DRP) is a progestin with antiandrogenic and antimineralcorticoid activity (20), and combined with EE it is effective in decreasing hirsutism and T levels and, more significantly, increasing sex hormone-binding globulin (SHBG) levels in women with PCOS (21,22).…”
mentioning
confidence: 99%
“…However, the metabolic effects of pills are extremely variable, depending on the dose of ethinyl E 2 (EE) and on the type of progestin associated. Drospirenone (DRP) is a progestin with antiandrogenic and antimineralcorticoid activity (20), and combined with EE it is effective in decreasing hirsutism and T levels and, more significantly, increasing sex hormone-binding globulin (SHBG) levels in women with PCOS (21,22).…”
mentioning
confidence: 99%
“…Consequently, there is no change in fasting glucose: insulin ratio or, in other (20) stated that EE/DRSP might be considered neutral with respect to insulin resistance. Pehlivanov et al (21) reported that in Europe, the most widely used combined oral pill in women with PCOS is a combination of EE (35 mcg) and 2 mg cyproterone acetate. However, the present study shows that the EE/DRSP can be a reasonable alternative.…”
Section: Discussionmentioning
confidence: 99%
“…En un trabajo de Pehlivanov y cols. de 20 mujeres con SOP tratadas con EE 0.03 mg/drosperinona 3 mg, se observó una disminución del SFG de 2.55 puntos al compararlo con el basal luego de 6 ciclos de tratamiento 56 . Un estudio en pacientes con SOP encontró un 33% de disminución relativa en hirsutismo cuando se comparó EE/drosperinona con EE/desogestrel, incluso después de 6 meses de descontinuado el tratamiento 57 .…”
Section: Anticonceptivos Orales Combinados Con Progestinas Antiandrogunclassified